(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Aim: Criminal face recognition system helps in identifying the suspect and also helps in retrieving information about thesuspect. Innovative Deepface algorithm is used for the face recognition method. Materials and Methods: Face detection foridentifying the criminals is performed using Deep Face (N=10) over LBPH model (N=10) with Gpower of 80% and alpha=0.05, with split size of 70% and 30 % for training and testing model respectively. Results: It is found that the accuracy ofDeepface is 91.90% which is higher than the LBPH model 90.80% and attained the significance value of p=0.0294 (p<0.05),showing that there is a significant difference between the groups.. Conclusion: For the face identification purpose InnovativeDeepface algorithm is preferred than LBPH algorithm.